2018
DOI: 10.1105/tpc.18.00239
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: OST1 Activation by the Brassinosteroid-Regulated Kinase CDG1-LIKE1 in Stomatal Closure

Abstract: Crosstalk between signaling pathways is an important feature of complex regulatory networks. How signal crosstalk circuits are tailored to suit different needs of various cell types remains a mystery in biology. Brassinosteroid (BR) and abscisic acid (ABA) antagonistically regulate many aspects of plant growth and development through direct interactions between components of the two signaling pathways. Here, we show that BR and ABA synergistically regulate stomatal closure through crosstalk between the BR-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…ABA-induced stomatal closure depends on OST1 (Mustilli et al, 2002). What Kim et al (2018) found is that the ost1 mutant is also insensitive to BRmediated stomatal closure, phenocopying the cdl1 mutant. With these solid phenotypic characterizations on hand, they investigated a possible mechanism by which both CDL1 and OST1 mediate the stomatal response.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…ABA-induced stomatal closure depends on OST1 (Mustilli et al, 2002). What Kim et al (2018) found is that the ost1 mutant is also insensitive to BRmediated stomatal closure, phenocopying the cdl1 mutant. With these solid phenotypic characterizations on hand, they investigated a possible mechanism by which both CDL1 and OST1 mediate the stomatal response.…”
mentioning
confidence: 84%
“…Because the authors show that CDL1 is preferentially expressed in the leaf guard cells, this protein-protein interaction and eventual transphosphorylation mechanism indicate that BR and ABA cooperate in a synergistic manner in modulating the stomatal closure response. (Adapted from Kim et al [2018], Figures 4A and 4B…”
Section: Cdl1-ost1mentioning
confidence: 99%
See 1 more Smart Citation
“…More intriguingly, photosynthesis rate was found to be declined under drought stress, especially in drought sensitive genotype, suggesting that the enhancement of antioxidant capacity was in favor of maintaining higher photosynthetic activity, and thereby would improve drought resistance of plants (Zhang et al 2016). Moreover, phytohormone signaling and Ca 2+ signaling were also highlighted in transcript pro ling and revealed the cross-talk among phytohormone signaling pathways (Kim et al 2018;LY et al 2014). In addition, a large number of transcription factor families, like WRKY, bZIP, and MYB, were identi ed involved in ABA-mediated signaling transduction under abiotic stresses (Borah et al 2017;Okay et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the photosynthesis rate was found to decline under drought stress, especially in drought-sensitive genotypes, suggesting that the enhancement of antioxidant capacity favors maintaining a higher photosynthetic activity and thereby improves the drought resistance of plants [36]. Moreover, phytohormone signaling and Ca 2+ signaling have also been highlighted in transcript pro ling and have been revealed cross-talk among phytohormone signaling pathways [37,38]. In addition, a large number of transcription factor families, such as WRKY, bZIP, and MYB families, were found to be involved in ABA-mediated signal transduction under abiotic stress [39,40].…”
mentioning
confidence: 99%